Microscopic and molecular evidence in support of rodent as a reservoir for dissemination of Leishmaniasis. Issue 7 (6th March 2020) - Khan, Imran; Noor, Zohaib; Allauddin Khan, Syed; Ali Khan, Taj; Muhammad, Niaz; Ullah Khattak, Bahar; Hussain, Mubashir
Abstract: Leishmaniasis is a worldwide public health problem and vector‐borne disease. It is caused by a diverse group of protozoan parasites that belong to the genus Leishmania and transmitted to humans through a bite of an infected female sand fly. Leishmaniasis has attained epidemic proportion in Khyber Pakhtunkhwa and raises serious concern over its management. The present research work was conducted in cutaneous leishmaniasis (CL) prevalent village named Surgul of district Kohat, Khyber Pakhtunkhwa with a focus to investigate whether rodent can act as a source for dissemination of leishmanial species or not. In this context, rodent samples were analyzed via morphological and molecular approaches to unveil prevalence of CL. It was reported that 12.5% of samples were positive for signs of leishmaniasis through microscopy and 18.75% through polymerase chain reaction (PCR). Supporting the findings further, the color character of rodents was also taken into consideration, which shows that light dark colored rodents were more infected (13.3%) compared to brown colored rodents (11.43%). Based on our findings, we speculate that small rodents are a possible reservoir of various leishmanial parasites and play a significant role in zoonosis and maintenance of their species. Abstract : Leishmania parasite was more prone toward the male mouse as a reservoir host, more compared to female. Evaluating the color‐based host occupancy, light dark mice were more susceptible. PCR and microscopic study revealed positive results for Leishmania parasite in the mice.